Er: YAG Laser Minimally Invasive Tooth Extraction - Wenjun Ouyang; Jiang Tao (Dental Hypotheses)
Introduction: Er: YAG laser has characteristics such as efficient cutting, promoting healing, controlling inflammation, and reducing pain, making it widely used in the resection of oral soft and hard tissue. The Hypothesis: Conventional tooth extraction may result in alveolar bone resorption, infection, bleeding, and pain. Most minimally invasive extraction methods aim to sever the periodontal ligament while reducing lateral pressure. The Er: YAG laser can remove oral soft and hard tissues with minimal heat-induced damage. Therefore, we propose the hypothesis that using the Er: YAG laser to assist in cutting periodontal soft and hard tissues during minimally invasive tooth extraction could not only improve extraction efficiency but also reduce intraoperative and postoperative complications, potentially ushering in a new era for minimally invasive extractions. Evaluation of the Hypothesis: The Er: YAG laser has demonstrated benefits in cutting efficiency, reducing bleeding, promoting healing, controlling inflammation, and alleviating pain in oral soft and hard tissue surgeries. A few studies have explored its use in severing the periodontal ligament near the tooth neck to assist in extractions. Therefore, we speculate that by increasing the laser power and adjusting other parameters, it may be possible to achieve a greater and deeper severance of the periodontal ligament, thereby accomplishing the goal of minimally invasive tooth extraction.